TD3-based energy management strategy for hybrid energy storage system of electric vehicle - Jiacheng LIU; Xiangwen ZHANG (智能科学与技术学报)
Combining batteries and super capacitors into a composite power system (CPS) with an effective energy management strategy can significantly improve the energy utilization, and increase the service life of the energy storage system.To minimize the energy loss of the system, an energy management strategy based on the twin delayed deep deterministic policy gradient (TD3) algorithm was designed.Compared with the deep deterministic policy gradient (DDPG) algorithm, TD3 algorithm solved the problem of overestimation of Q value and less energy loss.A MATLAB/Simulink simulation model based on the TD3 algorithm was built, and tested with the electric vehicle driving equation and the equivalent circuit model of CPS.The outcomes indicate that the proposed energy management strategy can effectively reduce the impact of high current on the battery, and compared with DDPG algorithm, the energy utilization efficiency is improved by 1.36%, the peak of output current of the battery is reduced by 14.68%, the temperature rise of the battery is reduced by 3.52%, the total energy consumption of the system is reduced by 2.17%.